Active travel and paratransit use in African cities: Mixed-method systematic review and meta-ethnography. (January 2023) - Randall, Lee; Brugulat-Panés, Anna; Woodcock, James; Ware, Lisa Jayne; Pley, Caitlin; Abdool Karim, Safura; Micklesfield, Lisa; Mukoma, Gudani; Tatah, Lambed; Dambisya, Philip Mbulalina; Matina, Sostina Spiwe; Hambleton, Ian; et al.
Abstract: Active travel, as a key form of physical activity, can help offset noncommunicable diseases as rapidly urbanising countries undergo epidemiological transition. In Africa a human mobility transition is underway as cities sprawl and motorization rises and preserving active travel modes (walking, cycling and public transport) is important for public health. Across the continent, public transport is dominated by paratransit, privately owned informal modes serving the general public. We reviewed the literature on active travel and paratransit in African cities, published from January 2008 to January 2019. We included 19 quantitative, 14 mixed-method and 8 qualitative studies (n = 41), narratively synthesizing the quantitative data and meta-ethnographically analysing the qualitative data. Integrated findings showed that walking was high, cycling was low and paratransit was a critical mobility option for poor peripheral residents facing long livelihood-generation journeys. As an indigenous solution to dysfunctional mobility systems shaped by colonial and apartheid legacies it was an effective connector, penetrating areas unserved by formal public transport and helping break cycles of poverty. From a public health perspective, it preserved active travel by reducing mode-shifting to private vehicles. Yet many city authorities viewed it as rogue, out of keeping with the 'ideal modern city', adopting official anti-paratransit stances without necessarily considering the contribution of active travel to public health. The studies varied in quality and showed uneven geographic representation, with data from Central and Northern Africa especially sparse; notably, there was a high prevalence of non-local authors and out-of-country funding. Nevertheless, drawing together a rich cross-disciplinary set of studies spanning over a decade, the review expands the literature at the intersection of transport and health with its novel focus on paratransit as a key active travel mode in African cities. Further innovative research could improve paratransit's legibility for policymakers and practitioners, fostering its inclusion in integrated transport plans. Highlights: Noncommunicable diseases are rising in Africa as populations urbanise and motorise. To offset this, active travel (walking, cycling, public transport) is desirable. Paratransit (informal public transport) is a key mode for urban African residents. Despite limited formal public transport many city authorities are anti-paratransit. Further paratransit research can foster more effective integrated mobility systems.